High-resolution mapping of the Drosophila fourth chromosome using site-directed terminal deficiencies. - Sousa-Neves, R.; Lukacsovich, T.; Mizutani, C.M.; Locke, J.; Podemski, L.; Marsh, J.L. (Genetics, 2005)
For more than 80 years, the euchromatic right arm of the Drosophila fourth chromosome (101F-102F) has been one of the least genetically accessible regions of the fly genome despite the fact that many important genes reside there. To improve the mapping of genes on the fourth chromosome, we describe a strategy to generate targeted deficiencies and we describe 13 deficiencies that subdivide the 300 kb between the cytological coordinates 102A6 and 102C1 into five discrete regions plus a 200-kb region from 102C1 to 102D6. Together these deficiencies substantially improve the mapping capabilities for mutant loci on the fourth chromosome.